Strategi Pengembangan Pariwisata Halal di Kabupaten Padang Lawas Utara - Nur Ainun Siregar; Yusrizal Yusrizal; Nurul Jannah (ManBiz: Journal of Management and Business, 2024)
This research aims to find out the strategy for developing halal tourism in North Padang Lawas Regency, and how halal tourism is mapped. Where the method used in this research is a descriptive qualitative method. Using data collection methods, namely interview, observation and documentation methods. The analysis used is SWOT analysis, namely by looking for strengths, weaknesses, opportunities and threats in developing halal tourism in North Padang Lawas Regency. Based on the SWOT results that have been carried out, the highest value is obtained from the SO value, namely 3.014. Therefore, the SO strategy must be developed and implemented to the maximum extent possible in order to develop tourism in North Padang Lawas. halal tourism in North Padang Lawas Regency. The strategy for developing halal tourism in North Padang Lawas Regency has many strengths for developing halal tourism, where tourism development must be carried out in a focused and serious manner. The strengths that tourism in North Padang Lawas has to develop are the availability of food, places of worship for Muslims, how to dress for people who have covered their private parts, support from the government, as well as promoting halal tourism which will make it easier for people to know about tourism in Padang Regency. Old North.